Designing a Conceptual model for Evaluating the Performance of Software Developers in Fintech Organizations - Hassan Javadi; Fereshteh Amin (مدیریت دولتی)
ObjectiveSoftware developers occupy top ranks within fintech organizations, representing a significant portion of human capital costs. The complexity of software development tools, the application of specialized knowledge, diverse work attitudes, varying levels of interaction, team distribution, and individual differences in behavior and personality all contribute to making the performance management of software developers a distinct and challenging task in fintech organizations. Many fintech organizations consistently face challenges in their relationships with software developers, leading to a high turnover rate. This turnover not only results in the loss and transfer of valuable knowledge and experience outside the organization, thereby weakening its competitive position, but also causes stakeholder dissatisfaction and a significant waste of financial and credit resources. One of the primary reasons for these challenges is the absence of well-defined performance criteria tailored specifically to software developers in fintech. Although various studies have explored certain aspects of performance criteria, no comprehensive and integrated study has been undertaken in this regard. Consequently, this research endeavors to identify and analyze the effective components for evaluating the performance of software developers in fintech organizations.MethodsThis research examines the lived experiences of software developers within the framework of an interpretative paradigm using an inductive and strategic phenomenological approach. Twelve semi-structured, in-depth interviews were conducted with software developers who were selected through a snowball sampling method. The data extracted from these interviews were analyzed using the content analysis method, with the assistance of Maxqda software. In addition, the fuzzy Delphi method, coupled with a two-stage expert survey, was employed to confirm and rank the identified components. The statistical population during the fuzzy Delphi phase comprised 10 software engineering experts, who were selected through purposive sampling based on their expertise and experience in the field.ResultsThis research identified 197 primary codes from the semantic expressions gathered during the interviews, which were subsequently categorized into 12 sub-themes. These sub-themes, listed in order of priority, include teamwork, quality of produced software, customer satisfaction, documentation skills, participation in knowledge sharing, commitment to scheduling, mastery of production tools, participation in goal realization, compliance with organizational regulations, adherence to technical standards, problem-solving ability, and frequency of software rewriting. These criteria were further classified into three overarching dimensions: technical, individual, and organizational. The findings underscore the intricate nature of performance evaluation, highlighting the multifaceted factors that must be considered when assessing the effectiveness of software developers in fintech settings.ConclusionBased on the life experiences and insights of software developers, the research findings indicate that non-technical components, such as teamwork and customer satisfaction, carry more weight and importance in performance evaluation compared to purely technical skills. The occurrence of organizational conflicts and dissatisfaction in fintechs is often rooted in the lack of transparency regarding financial and non-financial obligations between software developers and fintech organizations. Therefore, establishing clear, agreed-upon performance criteria among all stakeholders can significantly improve satisfaction, retention, and overall performance of software developers. This approach not only enhances organizational stability but also contributes to the long-term success and competitiveness of fintech organizations.